Literatura de testemunho e cinema : uma análise de batismo de sangue - Juchem, Vinícius Viana (Universidade do Vale do Rio dos Sinos, 2019)
The present thesis fits into a historiographical field that increasingly attracts researchers in Brazil and abroad: the History of the Present Time (HTP). It is a time frame that privileges relatively recent events and may include historical sources that reflect the technological development of the twentieth century. In this sense, witness literature and cinema are historical sources that allow us to analyze the memory of resistance built on the military dictatorship (1964-1985). Published in 1982, Frei Betto's book Baptism of Blood is a story that reveals the reasons for the approach of the Dominican friars to the armed struggle, questions the circumstances of the death of Carlos Marighella, leader of the National Liberating Action (ALN), and describes the psychological trauma that led Frei Tito to commit suicide. Public and critical success, Baptism of blood is today pointed as a reference in the Brazilian witness literature because it denounces the arbitrariness and violence committed by repression, with emphasis on one of the symbols of the military dictatorship: the torturer Sérgio Paranhos Fleury. A quarter of a century after its first edition, Frei Betto's book was adapted for film by director Helvécio Ratton to reveal to a new generation of Brazilians this relatively little-known chapter of the military dictatorship. The following question will guide scientific research: how was the narrative of the movie Blood Baptism constructed from the book of Frei Betto? The aim is to contribute to the set of studies on the history of the present time and the possible interpretations of cinema about the military dictatorship.
Keywords: História do Tempo Presente; Literatura de Testemunho; Ditadura Militar; Batismo de Sangue; History of the Present Time; Testimonial Literature; Military Dictatorship; Blood Baptism; ACCNPQ::Ciências Humanas::História